Varicella Susceptibility in a Canadian Population - Sam Ratnam (Canadian Journal of Infectious Diseases)
OBJECTIVE: To determine susceptibility to varicella zoster virus (VZV) infection among children, pregnant women and health care workers in Newfoundland.